Predictive Learning Powered by AI and Sophisticated Student Engagement Techniques - Mohd Bilal Khan; Ruchika Aggarwal (International Journal of Behavioral Sciences, 2026)
The contemporary landscape of education has witnessed a paradigm shift in integrating advanced technologies that have revolutionized the learning experience. Innovative methodologies have emerged to address longstanding challenges, such as enhancing student engagement, accurately predicting academic performance, and personalizing the learning journey. However, despite the numerous benefits that technology brings to education, there remains a crucial hurdle - sustaining student motivation and engagement. Traditional teaching methodologies often struggle to generate consistent interest and involvement among learners. To address this challenge, this research endeavors to examine a series of pioneering frameworks and algorithms that are designed to assess and improve student engagement and academic success. The research will focus on cutting-edge approaches that leverage artificial intelligence (AI), machine learning (ML), and gamification strategies. These technologies enable the creation of personalized learning experiences that can cater to the unique needs and preferences of individual learners. By analyzing learner data, such as their learning style, pace, and progress, these approaches can provide targeted feedback and recommendations to help learners achieve their academic goals. This research aims to contribute to the ongoing efforts to enhance the quality of education by exploring state-of-the-art approaches that can enhance student engagement, predict academic performance accurately, and provide personalized learning experiences.The interdisciplinary exploration in this research covers several key aspects. Firstly, it looks at hybrid gamification, AI tutoring frameworks, and the Adaptive Neuro-Fuzzy Inference System (ANFIS). These methodologies aim to create an immersive and personalized learning ecosystem by using AI-driven mechanisms to track, analyze and reward student performance and interactions, thus enhancing motivation and engagement levels. Hybrid gamification is a technique that combines game elements with traditional teaching methods. It uses game mechanics like points, badges, and leader boards to create a more engaging learning experience.
Keywords: Academic Performance Prediction; Hybrid Gamification; Personalized learning; artificial intelligence in education; student engagement